Niilismo, transvaloração e redenção na Filosofia de Nietzsche - Barbosa, Ildenilson Meireles (Universidade Federal de São Carlos, 2009)
Many are the productions already developed about nihilism in Nietzsche s work, wich the perspective of unconditional affirmation of the world and life is assumed as an inevitable consequence on the overcomig of nihilism itself. However, even admiting that Nietzsche s thougth about nihilism conducts him to an unconditional affirmation of every happening, our research is developed by the nitzschean notion of redemption. Since The Birth of Tragedy, Nietzsche explores the theme in the reconciliation fullfilled by the tragical art between the apollonian and dionisian.In his work of 1872, the philosopher finds in Dionysus shapes a god that affirms the suffering, wich is a crucial subject to the future guiding of his supreme-affirmative thought. In contrast to the tragical conception that was formed as a way to escape from the pessimism, the socratism-platonism is understood by Nietzsche as a movement that puts in progress the nihilist logical in the West, consummated on the christian conception of negativity. In front of a terrible diagnosis presented by Nietzsche in his works of maturity, we ve try to show in what measure on one hand, answering to the question about provenience of nihilism, in the other hand, explicitating it s developing on moderness, Nietzsche s philosophy is able to think radically on the overcomig of nihilism, reaching expressively in the project of transvaluation with the same notion of human s redemption.
Keywords: Filosofia alemã; Niilismo (Filosofia); Redenção; Platonismo; Nietzsche, Friedrich Wilhelm, 1844-1900; Transvaloração; Amor fati; Nihilism; Redemption; Transvaluation; Platonism; CIENCIAS HUMANAS::FILOSOFIA